Students’ Perception toward Using Canva in EFL Business Correspondence Class - Anita Dwi Hapsari (Edulitics (Education, Literature, and Linguistics) Journal, 2023)
Integration of ICT into ELT is something inevitable in this information era. This had been started years ago with the emergence of CALL. Now, with the ubiquity of mobile devices, MALL has started to emerge. This research analyzed the students’ perception of using Canva in Business Correspondence class. The researcher formulated the research problem as: How is the student’s perception toward using Canva in EFL Business Correspondence class? This could lead to other English lecturers realizing how useful* Canva is for Business Correspondence class. Additionally, it helps to evaluate the teaching and learning process to improve it going forward by seeing the viewpoints of the students. This study was a content analysis of qualitative research. Ten statements representing students’ opinions about using Canva served as the study’s instrument in the Business Correspondence class. The indicators are divided into three, they are usefulness, ease, and suitability of Canva for Business Correspondence class. The findings indicated that while 8,75% of students were neutral, 91,25% of all students agreed and strongly agreed that Canva is helpful for Business Correspondence classes. At that point, 95% of the students who agreed or strongly agreed that the Business Correspondence class would be easier for them overall received that score. In the Business Correspondence class, 91,67% of students responded positively about its applicability, with only 8,33% somewhat agreeing. In light of this, it can be said that Canva is a useful visual design tool that may be used in Business Correspondence classes. The study’s findings ought to shed light on the pedagogical implications of utilizing Canva in language teaching as well as the possible advantages of doing so from the student’s perception.